PJMHS 2022
DOI: 10.53350/pjmhs20221612512
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Topical 1% Adapalene Versus Cryotherapy in Treatment of Plantar Warts

Abstract: Background: Warts are spiny, rough papules or nodules that can be found anywhere on skin. They are caused by human papilloma virus (HPV) infection. There are over 100 HPV types documented. Approximately 6% of children and 2% of adults consult the doctor for wart. The aim of the current study was To compare the efficacy of topical Adapalene gel 0.1% under occlusion with cryotherapy in the treatment of plantar wart Methodology: It was Randomized control trial carried out at the Department of Dermatology, Combine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…One study observed that resolution of plane warts in 77.78% of cases by using adapalene; however they also reported adverse effects of adapalene in 13.6% of cases 18 . Another study found (75.68%) efficacy of adapalene in treatment of plantar warts and their complete clearance 19 . The results were comparable to the current study, the difference was that our study focused on plane warts but the results are comparable.…”
Section: Discussionmentioning
confidence: 98%
“…One study observed that resolution of plane warts in 77.78% of cases by using adapalene; however they also reported adverse effects of adapalene in 13.6% of cases 18 . Another study found (75.68%) efficacy of adapalene in treatment of plantar warts and their complete clearance 19 . The results were comparable to the current study, the difference was that our study focused on plane warts but the results are comparable.…”
Section: Discussionmentioning
confidence: 98%